2015
DOI: 10.1099/jmmcr.0.000098
|View full text |Cite
|
Sign up to set email alerts
|

A case of cutaneous penicilliosis in a child with acute myeloid leukaemia

Abstract: Introduction: We present a case of cutaneous penicilliosis in a paediatric patient with acute myeloid leukaemia (AML). Case report: A 2-year-old boy with AML first developed probable pulmonary aspergillosis during induction chemotherapy in an overseas centre in May 2013, and was treated with AmBisome and voriconazole. When he was admitted to our centre with relapsed AML in October 2013, he was given a fifth course of chemothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 9 publications
1
9
1
Order By: Relevance
“…We considered P. citrinum infection in our patient for the following reasons: (i) The growth of P. citrinum in five separate sputum cultures from a symptomatic patient with uncontrolled DM prompted careful consideration of a P. citrinum pneumonia; (ii) Pathological biopsy revealed small abscesses and granulomatous nodules, and special stain (PAM) result was positive, suggesting fungal pneumonia; (iii) There was no evidence to confirm infection of other organisms. GM test in BAL fluid was negative which is in contrast with previous reports [15,16]. It's likely that our patient was nonagranulocytosis and received voriconazole, to which false-negative GM test results have been attributed.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…We considered P. citrinum infection in our patient for the following reasons: (i) The growth of P. citrinum in five separate sputum cultures from a symptomatic patient with uncontrolled DM prompted careful consideration of a P. citrinum pneumonia; (ii) Pathological biopsy revealed small abscesses and granulomatous nodules, and special stain (PAM) result was positive, suggesting fungal pneumonia; (iii) There was no evidence to confirm infection of other organisms. GM test in BAL fluid was negative which is in contrast with previous reports [15,16]. It's likely that our patient was nonagranulocytosis and received voriconazole, to which false-negative GM test results have been attributed.…”
Section: Discussioncontrasting
confidence: 94%
“…Voriconazole should not be considered first-line for the empiric treatment of P. citrinum [16]. The high MIC of P. citrinum isolate in our patient, which is consistent with previous reports [15,16,22], may partly explain why the initial administration of voriconazole was ineffective. Therefore, early antifungal susceptibility testing is essential for appropriate treatment to improve clinical outcomes.…”
Section: Discussionsupporting
confidence: 87%
“…Only one of the 4 published case reports of P. citrinum infections reported a voriconazole MIC. That MIC was also above the limits of quantification, albeit at > 256 μg ml −1 [8]. The only other report of P. citrinum sensitivities encountered after a broad literature search was authored by a group at the Fungal Testing Laboratory at the University of Texas Health Science Center [11].…”
Section: Discussionmentioning
confidence: 98%
“…We performed an extensive literature search identifying a total of four reports of P. citrinum infection in humans, three of which occurred in patients with acute leukemia receiving intensive chemotherapy [6] , [7] , [8] and one which occurred in the setting of direct inoculation into an immune-privileged space [9] . Based on our patient's significantly milder degree of immunocompromise relative to that induced by acute leukemia plus chemotherapy, we concluded that P. citrinum was unlikely to have been a tissue-invasive cause of pneumonia in her case.…”
Section: Introductionmentioning
confidence: 99%
“…P. citrinum has been reported to be a human-opportunistic pathogen responsible for keratitis, cutaneous infections, and pneumonia (25)(26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%